Interaction Between Home and School: The Views of Teachers and Parents from Finland and Russia - Sormunen, Marjorita; Kirilina, Valentina; Goranskaya, Svetlana; Tossavainen, Kerttu (International Journal about Parents in Education, 2023)
This study undertaken as part of the project AHIC (Addressing Challenging Health Inequalities of Children and Youth between two Karelias 2013-2014), aimed to explore the interaction between home and school from a cross-cultural perspective. The study sample comprised 60 parents and 18 teachers from two schools in North Karelia, Finland, and 154 parents and 51 teachers from two schools in the Republic of Karelia, Russia, in May 2013 using questionnaires. The results indicated that teachers on both sides of the border had quite similar views about the interaction between home and school. Parents’ views, instead, differed more between the countries, since Finnish parents viewed the characteristics of home-school collaboration more positively than Russian parents did. Comparisons within the countries reveal that parents and teachers in both countries held several contradictory views about home-school collaboration, mainly in the areas of communication and parents’ participation (Finland), and in the areas of parents’ role and participation in the school community (Russia). The findings underline that in-service training for teachers is recommended to help them recognise the different characteristics for efficient home-school collaboration and include them into their everyday work. School procedures involving parents in the school community needs to be clarified.